Multi‐MeV Electron Dynamics Near the Inner Edge of the Outer Radiation Belt. Issue 23 (2nd December 2021) - Hogan, Benjamin; Li, Xinlin; Zhao, Hong; Khoo, LengYing; Jaynes, Allison; Kanekal, Shrikanth; Blake, J. Bernard; Baker, Daniel N.
Abstract: A variety of dynamic behavior of multi‐MeV electrons near the inner edge of the outer radiation belt has been revealed by detailed analysis of Van Allen Probes data. This study presents multi‐MeV electron flux and phase space density (PSD) using Van Allen Probes data during two strong geomagnetic storms to reveal their energy‐dependent dynamics in the outer belt, with dynamics occurring on timescales of hours to ∼1 week. Enhancements are shown down to L = 2.6, where ∼3 MeV electron populations are enhanced by an order of magnitude during one storm of study. Study of a second comparable storm shows rapid depletion of electron populations up to ∼7 MeV in the region 2.6 ≤ L ≤ 3. We also identify a local electron PSD peak at L ≈ 3 that slowly accumulates during quiet time and is rapidly depleted during an intense storm. Possible contributors to these dynamics are discussed. Plain Language Summary: Electrons in Earth's magnetic field, or magnetosphere, form into two bands known as the Van Allen radiation belts. The Van Allen Probes mission consisted of two satellites to measure energetic particle flux in these belts. Based on early studies of the first 2 years of data from the mission, it was first believed that along the inner edge of the outer belt, there was a barrier to multi‐MeV electrons, with physical mechanisms of this barrier yet to be understood. Further studies have revealed that multi‐MeV electrons can be dynamic more Earthward than originally thought. This study shows that multi‐MeV electrons along the inner edge of the outer belt can be highly dynamic on rapid timescales, with a variety of behavior including enhancements or depletions that appear to be influenced by preconditioning of the Van Allen radiation belts. The strength of these dynamics is generally diminished with increased electron energy and decreased distance toward Earth. Additionally, a localized region of multi‐MeV electrons has been newly found by analyzing electron populations in coordinate systems mapped to the particles' motion. This population is then rapidly depleted during strong modification to the magnetosphere. The physical mechanisms influencing electron dynamics in the magnetosphere are discussed. Key Points: Multiple orders of magnitude dynamics of multi‐MeV electron flux and phase space density are shown near the inner edge of the outer belt These dynamics, and their timescales, appear to be energy‐dependent, with variations on the timescales of hours to one week within L ⪅ 3 Quiet‐time formation of a local peak at L ≈ 3 of ⪆6 MeV electron phase space density and its rapid decay during storms are shown